Partial Resuscitative Endovascular Balloon Occlusion of the Aorta and Intermittent Resuscitative Endovascular Balloon Occlusion of the Aorta - Hitomi, Suguru; Kurihara, Yutaro; Maruhashi, Takaaki; Matsumura, Yosuke (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a resuscitation procedure for severe hemorrhagic shock. While complete occlusion of the aorta could be effective for the control of blood flow, there is always a concern for ischemia-reperfusion injury of the distal organs from the balloon catheter. REBOA can control the degree of occlusion by changing the injection volume of the balloon catheter. Partial REBOA and intermittent REBOA are some of the strategies of REBOA, with which less ischemia-perfusion injury is done, rather than complete occlusion of the aorta, although evidence on partial REBOA and intermittent REBOA is still limited. This review aims to share the practical knowledge of partial REBOA and intermittent REBOA, thorough the current literature and Japanese multi-specialty expert consensus.